A Guardian Angel Gone Astray: How Not to Engage in Scientific Debates - Nahm, Michael (Journal of Scientific Exploration, 2023)
In a recent commentary on an essay competition regarding the best evidence for the survival of human consciousness, Keith Augustine prominently criticized the award-winning essay I submitted to this competition. As demonstrated in the present article, Augustine’s critique is specious as evidenced by specifically two aspects of it: 1) On multiple occasions, Augustine misrepresented contents of my essay by attributing statements to me I never made and by presenting quotes out of context and contorting their original meaning. Due to Augustine’s misrepresentations of my essay’s content, it is unavoidable to conclude that his entire commentary is permeated by biased reasoning. 2) Although Augustine caviled at numerous formulations he drew from all over my essay, he did not mention that I singled his work out for profound criticism on numerous pages of my essay. He did not even attempt to counter my critique of his writings on factual grounds. In conclusion, Augustine’s commentary is a good example of a bad contribution to the survival debate.